A critical analysis of managing change for the accounting cadre at the treasury department in Lesotho - Mosoeunyane, Tlali Zechariah (University of the Free State, 2014)
Abstract not available
Dissertation (MBA (Business Administration)) --University of the Free State, 2014
Keywords: Organizational change; Accounting; Organizational behavior